2024
DOI: 10.1590/1519-6984.255605
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability analysis in bitter gourd (Momordica charantia L.) for potential quality improvement

Abstract: Combining ability analysis provides useful information for the selection of parents, also information regarding the nature and magnitude of involved gene actions. Crops improvement involves strategies for enhancing yield potentiality and quality components. Targeting the improvement of respective characters in bitter gourd, combining ability and genetic parameters for 19 characters were estimated from a 6×6 full diallel analysis technique. The results revealed that the variances due to general combining abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…Thus these lines show the presence of additive gene action and could be used in multiple crossing to develop synthetics and for the isolation of elite inbred lines and as a potent source for improving the economic traits in bitter gourd. Similar work has been carried out by various researchers viz; Ashwini, B [20], Kundu et al [21], Bhatt et al [16], Khan et al [22], Kaniti [23], Sridhar and Mulge [15], Dey et al [24], Jadhav et al [25]. It was observed that the parental lines which were high performing were also good general combiners for the respective characters.…”
Section: Combining Ability Effectssupporting
confidence: 68%
See 1 more Smart Citation
“…Thus these lines show the presence of additive gene action and could be used in multiple crossing to develop synthetics and for the isolation of elite inbred lines and as a potent source for improving the economic traits in bitter gourd. Similar work has been carried out by various researchers viz; Ashwini, B [20], Kundu et al [21], Bhatt et al [16], Khan et al [22], Kaniti [23], Sridhar and Mulge [15], Dey et al [24], Jadhav et al [25]. It was observed that the parental lines which were high performing were also good general combiners for the respective characters.…”
Section: Combining Ability Effectssupporting
confidence: 68%
“…Therefore, the best option for improvement is the identification of transgressive segregants which may lead to isolation of promising high yielding lines in bitter gourd [29]. These results are in conformity with those of Kundu et al [21], Balat et al [30] for bottle gourd; Acharya et al [13], Bhatt et al [16] , Kopped et al [31], Laxuman et al [32] and Kaniti [23] for various yield attributes in bitter gourd. [13], Jadhav et al [25], Laxuman et al [32], Verma et al [33] in bitter gourd; Naliyadhara et al [34] in sponge gourd; Narasannavar et al [35] and Muthaiah et al [36] in ridge gourd; Kamer et al [37] in melon.…”
Section: Combining Ability Effectssupporting
confidence: 64%
“…The common approach to selecting parents based on performance does not necessarily lead to the best 1252 (2023) 012077 IOP Publishing doi:10.1088/1755-1315/1252/1/012077 2 outcomes in a hybrids program [6]. Full diallel cross analysis provides estimates of genetic parameters involved in combining abilities as well as a rapid overall picture of the dominant relationship of parents to the resulting F1 [7]. And because cucumbers are an important crop that can be grown all over the country, there are still problems related to poor production, lack of reliance on locally produced seeds and the high cost of imported ones, as well as the lack of production of hybrid seeds that are tolerant to environmental stresses [8].…”
Section: Introductionmentioning
confidence: 99%